Ridge and Transverse Correlation without Long-Range Longitudinal Correlation - Charles B. Chiu; Rudolph C. Hwa (Advances in High Energy Physics)
A simple phenomenological relationship between the ridge distribution in Δη and the single-particle distribution in η can be established from the PHOBOS data on both distributions. The implication points to the possibility that it is not necessary to have long-range longitudinal correlation to explain the data. An interpretation of the relationship is then developed, based on the recognition that longitudinal uncertainty of the initial configuration allows for non-Hubble-like expansion at early time. It is shown that the main features of the ridge structure can be explained in a model where transverse correlation stimulated by semihard partons is the principal mechanism. This work is related to the azimuthal anisotropy generated by minijets in Au-Au collisions at 0.2 TeV on the one hand and to the ridge structure seen in pp collisions at 7 TeV on the other hand.